Pengenalan Robotika Yang Ergonomi Untuk Siswa SMK 10 Nopember Jakarta - Diah Utami; Puspita Dewi Widayat; Rikko Putra Youlia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Robotics is a field that combines engineering, electronics, and programming to design and control robots. In the introductory robotics program at SMK 10 Nopember Jakarta, students will learn the basics of robotics, including the main components of robots, how automated systems work, and programming to operate robots. Forty-four students attended. The goal of this activity was to increase students' understanding of robotics technology, encourage creativity in technological innovation, and provide practical skills applicable to the automation and technology industries. With project-based learning, students will have the opportunity to design and build a simple robot. Students successfully built the robot, but some were unable to due to time constraints, so we provided video tutorials for them to work on outside of school hours.